2024
DOI: 10.1039/d3py01172k
|View full text |Cite
|
Sign up to set email alerts
|

Towards the universal use of DOSY as a molar mass characterization tool: temperature dependence investigations and a software tool to process diffusion coefficients

Igor W. F. Silva,
Alasdair McKay,
Anna Sokolova
et al.

Abstract: Two aspects of molar mass determination via diffusion ordered spectroscopy (DOSY) are described in this work. Firstly, we investigated in how far the temperature of measurement affects the outcome of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…This results in the higher temperatures used in the MaDDOSY calibration no longer holding true, and as such, the calibration should be used with caution. The effects of this can be somewhat mitigated due to the viscosity correction, provided the viscosity at the given temperature is known and convection correction is accounted for . For the reaction studied here, conducted at 70 °C, the viscosity of dioxane was determined experimentally.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…This results in the higher temperatures used in the MaDDOSY calibration no longer holding true, and as such, the calibration should be used with caution. The effects of this can be somewhat mitigated due to the viscosity correction, provided the viscosity at the given temperature is known and convection correction is accounted for . For the reaction studied here, conducted at 70 °C, the viscosity of dioxane was determined experimentally.…”
Section: Resultssupporting
confidence: 69%
“…The measured diffusion constant can be correlated with the molecular weight of the macromolecule, and indeed, this has been shown in previous works , and further developed into a universal calibration within our groups …”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…As a point of comparison, Silva et al have recently reported using the dstebpgp3s pulse sequence to expand the usable temperature window of the measurement. 28…”
Section: Resultsmentioning
confidence: 99%
“…21 DOSY has already been shown as excellent tool for analysing the molecular weights of polymers. 22–29 It is non-invasive and requires extremely small amounts of material. It can even be performed on benchtop spectrometers to give rapid and convenient measurements.…”
Section: Introductionmentioning
confidence: 99%